Peran Kepala Madrasah dalam Meningkatkan Mutu Pendidikan Melalui Manajemen Berbasis Sekolah di MI Roudlotul Jannah Islamic Bilingual Scholl Prambon Sidoarjo - Mifta Alfiyana Nashihah; Zakariyah Zakariyah; Ashari Ashari (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study describes the role of leadership in improving the quality of education through School Based Management which is applied at S MI Roudlotul Jannah Prambon with the formulation of the research problem: What is the role of leadership in improving the quality of education, What are the supporting and inhibiting factors in improving the quality of education through School Based Management . The method used is a qualitative approach with a case study approach. Data collection techniques are used by observation, interviews and documentation studies. Data analysis techniques are made by data reduction, data display and conclusion (verification) and data validity. The results of this study indicate that school principals have implemented SBM to improve the quality of education with the following activities: First, madrasah heads have planned and evaluated school programs, curriculum management and teaching and learning processes, student services, human resource management, financial management, facility management and Infrastructure and School-Community Relations. Second; the head of the madrasa plays a role as; Supervisors, Managerial and Educators thus the leadership role of the head of the madrasa at MI Roudlotul Jannah in order to improve the quality of education, has been quite well demonstrated by the graduation standards which increase every year. Third; supporting and inhibiting factors include: Supporting: Visionary Leadership, Qualified Teachers, Relevant Curriculum, Parental and Community Participation and Adequate Facilities; Barriers: Technology and Globalization Challenges, Lack of Funding Sources, Inadequate Evaluation and Monitoring, Lack of Access to Technology and Infrastructure.